2014
DOI: 10.3390/ijerph111010182
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Access to Health Services of the Immigrant and Native-Born Population in Spain in the Context of Economic Crisis

Abstract: Aim: To analyze changes in access to health care and its determinants in the immigrant and native-born populations in Spain, before and during the economic crisis. Methods: Comparative analysis of two iterations of the Spanish National Health Survey (2006 and 2012). Outcome variables were: unmet need and use of different healthcare levels; explanatory variables: need, predisposing and enabling factors. Multivariate models were performed (1) to compare outcome variables in each group between years, (2) to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 33 publications
3
40
2
1
Order By: Relevance
“…Despite the restrictions and cutbacks applied, analysis of the data obtained in national health surveys in 2006 (pre-crisis) and 2011-12 (mid-crisis) reveals no deterioration in immigrants' access to health care or in their health status, compared to persons with Spanish nationality [15]. The 2011 survey was conducted prior to the adoption of RDL 16/2012.…”
Section: Impact On Healthcare Service Access and Uptakementioning
confidence: 99%
“…Despite the restrictions and cutbacks applied, analysis of the data obtained in national health surveys in 2006 (pre-crisis) and 2011-12 (mid-crisis) reveals no deterioration in immigrants' access to health care or in their health status, compared to persons with Spanish nationality [15]. The 2011 survey was conducted prior to the adoption of RDL 16/2012.…”
Section: Impact On Healthcare Service Access and Uptakementioning
confidence: 99%
“…As a result of the financial crisis affecting Spain from 2008, various austerity and cost-containment measures were introduced into the health and social welfare system. One change, introduced after our survey was conducted, was the restriction of access to health care among undocumented migrants (and others considered to be uninsured under the universal, residence permit-based system) to emergency and ante- and post-natal care only 29 . The implication is likely to be more severe restrictions than the already significant restrictions we observe in our results.…”
Section: Discussionmentioning
confidence: 70%
“…Several studies analysed public hospital utilisation by foreign residents in Spain, specially focusing on immigrant population [ 33 , 34 , 35 ]. In general, previous studies found lower rates of utilisation, which were attributed to age and better health conditions among the immigrant population [ 11 , 36 , 37 ]. However, given that average utilisation rates by immigrants are not comparable to those by pensioners; more research focussed on specific groups among foreign residents is required.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in Europe there are not these kinds of analyses in spite of the increasing mobility of patients. With the exception of some specific subjects, e.g., the analysis of healthcare resources required by economic immigrants [ 11 ], the literature related to patients mobile throughout Europe is still in its infancy [ 6 ]. Rosenmöller et al [ 2 ] propose five categories of mobile patients in Europe: (1) citizens on holidays, (2) pensioners or retired long-term residents, (3) cross-border care, (4) medical travellers and (5) people sent abroad by their national healthcare system [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%